Taklim Assembly in Padangsidimpuan 1901-2020: History of Non-Formal Islamic Education - Fauziah Nasution; Haidar Putra Daulay; Hasan Asari Asari (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to produce an analytical-critical formulation about the history of the rise of non-formal Islamic educational institutions: the taklim assembly in Padangsidimpuan in 1901-2020. This study uses a social history approach, by classifying time, as a historical explanation method. The data sources consist of: material and verbal sources. Data obtained through interviews, observation and documentation. The research was conducted in Padangsidimpuan City in 2020, with stages: topic selection, data collection, verification, interpretation and historiography. The results of this study found that: Majelis taklim in Padangsidimpuan experienced a revival in the 1901-2020 period. In terms of quantity, in 2020 the taklim assembly in Padangsidimpuan reached 189, while in quality it was marked by the development of the taklim assembly component. The taklim method in the 1901-2020 period did not experience significant development. The majority of Ustadz use the lecture method; relying on hearing and sight. As for the urban taklim assemblies with special material studies using a combined method, namely; method of lecture, discussion, note-taking, practice and question and answer. The development of taklim material is marked by the enrichment of taklim material from monotheism, which then develops into the material of fiqh worship and muamalah as well as other social problems. The development of taklim material was then marked by the transition of material about practical practices to the study of legal sources (Tafsir and Hadith).